2012
DOI: 10.1021/nl300316f
|View full text |Cite
|
Sign up to set email alerts
|

Chiroptical Effects in Planar Achiral Plasmonic Oriented Nanohole Arrays

Abstract: Chiroptical effects are routinely observed in three dimensional objects lacking mirror symmetry or quasi-two-dimensional thin films lacking in-plane mirror symmetry. Here we show that symmetric plasmonic planar arrays of circular nanoholes produced strong chiroptical responses at visible wavelengths on tilting them with respect to the incident light beam due to the collective asymmetric nature of their surface plasmon excitations. This extrinsic chiroptical effect can be stronger than the local chiroptical res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
88
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 28 publications
3
88
0
Order By: Relevance
“…For instance, Ben et aldemonstrated a ~4 times stronger optical chirality in achiral periodic nanoholes compared to the gammadion structure. 12 Recently, Abraham et. al.…”
mentioning
confidence: 99%
“…For instance, Ben et aldemonstrated a ~4 times stronger optical chirality in achiral periodic nanoholes compared to the gammadion structure. 12 Recently, Abraham et. al.…”
mentioning
confidence: 99%
“…Typically, it was thought that samples that produced CD had to be chiral, that is, they could not be superimposed with its mirror image 9 . However, recent experiments with planar mirror-symmetric plasmonic structures have shown that a non-zero CD can be obtained if the sample is illuminated at oblique angles [10][11][12][13] . Other attempts to create CD with a non-chiral sample have been carried out surrounding the sample with a chiral medium [14][15][16] .…”
mentioning
confidence: 99%
“…The research on chiral metasurfaces has covered an astoundingly large portfolio of designs, ranging from the initial famous gammadion shape meta-atom [ 16,28 ] to split-rings, [29][30][31] fi shshapes, [ 32 ] L-shape, [ 33 ] and achiral oriented structures, [34][35][36][37] and spanned the frequencies from visible to gigahertz(GHz). [ 38 ] For the purpose of chiral molecule sensing, [ 39,40 ] it is essential to achieve a pronounced chiral optical response in the UV to near-IR spectral range, where the resonant responses of most chiral molecules lie.…”
Section: A Novel Chiral Metasurface With Controllable Circular Dichromentioning
confidence: 99%
“…More importantly, because of the design complexity of the proposed chiral patterns and the enhancement mechanism being linked only to the localized mode, it is hard to tailor the chiral resonance by simply altering geometric parameters. [ 41 ] Although some pioneer work [ 35,36 ] on chiral metasurfaces linked the collective chiral responses to the propagating modes, there is still lack of clear demonstration. Consequently, the chiral responses shown in previous works were mostly spectrally fi xed, which severely limits practical applications.…”
mentioning
confidence: 99%